Estimation of Total Phenolic Content, Total Flavonoid Content, Anti-oxidant Activity and Molecular Docking Studies of Stereocaulon piluliferum Th. - Karki, Deepa; Phunyal, Anuraj; Adhikari, Achyut (Journal of Plant Resources, 2024)
Secondary metabolites, along with most compounds found in lichens, possess unique qualities that contribute significantly to combating various diseases. The present research study aimed to assess the estimation of total phenolic content, total flavonoid content and antioxidant activity of a methanolic extract and molecular docking of chemical compound present in Stereocaulon piluliferum Th. Fr. The total phenolic content of the lichen extract was determined using the Folin-Ciocalteu reagent method, while the total flavonoid content was assessed using the aluminum chloride method. Similarly, antioxidant activity was evaluated through DPPH free radical scavenging. S. piluliferum displayed notable levels of total phenolic and flavonoid content at 50.92593 ± 0.12 mg GAE/g and 9.888 ± 0.21 mg QE/g, respectively. The methanolic crude extract of S. piluliferum demonstrated potent antioxidant properties with an IC50 value of 111.95 ± 0.98 µg/mL. This study suggests that lichens, specifically S. piluliferum, could serve as a valuable natural source of antioxidants and showed the significant inhibition activity by exhibited a binding affinity of -8.5 kcal/mol of atranorin against alpha-glucosidase through computational analysis.